Rekonstruksi Konsep Syaż Dalam Kajian Hadis: Telaah Pemikiran Syaikh Abdullah Al-Ghumari - Afriza, Nugraha Andri; Nasution, Khairul Bahri (Jurnal Keislaman, 2024)
This research is based on the opinion of several Ulama who stated that researching the syaż of a hadiṡ is not an easy activity. The implication is that studies on syaż in the treasury of hadiṡ science have not experienced encouraging developments. This causes books that discuss hadiṡ containing syaż to be very difficult to find. Until finally the work of Sheikh Abdullah al-Ghumari appeared, which became the antithesis of this opinion. The purpose of this study is to determine the concept of syaż and the steps taken by Sheikh Abdullah Al-Ghumari in determining the syaż of a hadiṡ. This research is a descriptive qualitative type that compiles and explains the results of the study through words and sentences, not numbers. This study uses a library research method in data collection. The main source of information for this study is Sabil al-Tawfiq fi Tarjamati Abdullah bin al-Siddiq al-Ghumari. The data analysis used in this study is the thematic analysis. The results of this study, related to the steps taken by Sheikh Abdullah al-Ghumari in criticizing the hadiṡs that are considered syaż in general, are as follows: 1) Mentioning the mukharrij of the Hadiṡ; 2) Mentioning the status of the Hadiṡ as syaż and not allowed to be practiced; 3) Mentioning the reasons for its syaż either because it contradicts the mutawatir Hadiṡ, verses of the Qur'an, ijma', valid rules in the science of hadiṡ,, the weakness of the narrator, or because the Hadiṡ is munqathi' or mursal.